Performance Evaluation of Successive Interference Cancellation on Gain Ratio Power Allocation using Underwater Visible Light Communication Channel - Nur'Adli, Luthfi; Fahmi, Arfianto; Pamukti, Brian (JOIV : International Journal on Informatics Visualization, 2022)
Underwater Visible light communication (UVLC) is a network communication wirelessly where information is transmitted employing light through visible waves; in this case, the light source comes from a light-emitting diode (LED) as a transmitter underwater. VLC has several advantages over radio frequency technology, such as safer communication because light propagation cannot penetrate the wall, so it is difficult to do hacking, easy to get a license, relatively build cheap cost, and has no side effects on health. However, VLC has several limitations, one of which is the narrow bandwidth modulation. VLC undergoes a distribution of modulated bandwidth to allocate against each user. This bandwidth sharing has an impact on reduced system capacity. This study applied non-orthogonal multiple access (NOMA) to increase system capacity. This research analyzes the performance of the two best power allocation methods in a water medium, including gain ratio power allocation (GRPA) and static power allocation (SPA). In the results obtained in the NOMA-UVLC power allocation value, GRPA is more stable than SPA power allocation. Then applying residue in the successive interference cancellation (SIC) process will result in a decrease in system capacity compared to no residue in the SIC process. This study found that the GRPA power allocation is more stable in capacity performance compared to the application of SPA power allocation. Average capacity increase of 48.5% in GRPA power allocation